MicroRNA regulatory networks associated with abnormal muscle repair in survivors of critical illness. Issue 2 (28th January 2022) - Walsh, Christopher J.; Escudero King, Carlos; Gupta, Muskan; Plant, Pamela J.; Herridge, Margaret J.; Mathur, Sunita; Hu, Pingzhao; Correa, Judy; Ahmed, Sameen; Bigot, Anne; dos Santos, Claudia C.; Batt, Jane; et al.
Abstract: Background: Intensive care unit (ICU)‐acquired weakness is characterized by muscle atrophy and impaired contractility that may persist after ICU discharge. Dysregulated muscle repair and regeneration gene co‐expression networks are present in critical illness survivors with persistent muscle wasting and weakness. We aimed to identify microRNAs (miRs) regulating the gene networks and determine their role in the self‐renewal of muscle in ICU survivors. Methods: Muscle whole‐transcriptome expression was assessed with microarrays in banked quadriceps biopsies obtained at 7 days and 6 months post‐ICU discharge from critically ill patients ( n = 15) in the RECOVER programme and healthy individuals ( n = 8). We conducted an integrated miR–messenger RNA analysis to identify miR/gene pairs associated with muscle recovery post‐critical illness and evaluated their impact on myoblast proliferation and differentiation in human AB1167 and murine C2C12 cell lines in vitro . Select target genes were validated with quantitative PCR. Results: Twenty‐two miRs were predicted to regulate the Day 7 post‐ICU muscle transcriptome vs. controls. Thirty per cent of all differentially expressed genes shared a 3'UTR regulatory sequence for miR‐424‐3p/5p, which was 10‐fold down‐regulated in patients ( P < 0.001) and correlated with quadriceps size ( R = 0.86, P < 0.001), strength ( R = 0.75, P = 0.007), and physical function (Functional Independence Measures motor subscore, R = 0.92, P < 0.001) suggesting its potential role as a master regulator of early recovery of muscle mass and strength following ICU discharge. Network analysis demonstrated enrichment for cellular respiration and muscle fate commitment/development related genes. At 6 months post‐ICU discharge, a 14‐miR expression signature, including miRs‐490‐3p and ‐744‐5p, identified patients with muscle mass recovery vs. those with sustained atrophy. Constitutive overexpression of the novel miR‐490‐3p significantly inhibited AB1167 and C2C12 myoblast proliferation (cell count AB1167 miR‐490‐3p mimic or scrambled‐miR transfected myoblasts 7926 ± 4060 vs. 14 159 ± 3515 respectively, P = 0.006; proportion Ki67‐positive nuclei AB1167 miR‐490‐3p mimic or scrambled‐miR transfected myoblasts 0.38 ± 0.07 vs. 0.54 ± 0.06 respectively, P < 0.001; proliferating cell nuclear antigen expression AB1167 miR‐490‐3p mimic or scrambled‐miR transfected myoblasts 11.48 ± 1.97 vs. 16.75 ± 1.19 respectively, P = 0.040). Constitutive overexpression of miR‐744‐5p, a known regulator of myogenesis, significantly inhibited AB1167 and C2C12 myoblast differentiation (fusion index AB1167 miR‐744‐5p mimic or scrambled‐miR transfected myoblasts 8.31 ± 7.00% vs. 40.29 ± 9.37% respectively, P < 0.001; myosin heavy chain expression miR‐744‐5p mimic or scrambled‐miR transfected myoblasts 0.92 ± 0.39 vs. 13.53 ± 5.5 respectively, P = 0.01). Conclusions: Combined functional transcriptomics identified 36 miRs including miRs‐424‐3p/5p, ‐490‐3p, and ‐744‐5p as potential regulators of gene networks associated with recovery of muscle mass and strength following critical illness. MiR‐490‐3p is identified as a novel regulator of myogenesis.